INFLUENCE OF FEEDBACK MECHANISM ON STUDENTS' PERFORMANCE IN ECONOMICS IN KOGI STATE, NIGERIA (2007)
This paper discusses formative or developmental evaluation whose results, when used asfeedback mechanism, would lead to improvement of students' academic performance at the secondary school level, Two questions were asked on the use and influence of feedback mechanism on students' academic .. performance, A ten-tem checklist was used tofind answers to the questions, while 20 teachers were interviewed on the subject of the investigation. The data we're collected from continuous assessment as well as the Senior School Certificate Examination result of two sess ions (1999-2001). The data were analysed using frequency counts and using percentages, Correlationstatistic was also used to answer the hypothesis so postulated for the purpose of the study. Theperformance in economics bystudents wasfound to have improved appreciably. Some recommendations were made for effective use offeedback mechanism for better results in secondary schools. They include adequate funding the encouragement offrequent use of formative evaluation to provide feedback on students' performance; it was also recommended that organization of seminars on formative evaluation and feedback for teachers among others be undertaken at regular intervals.